2017
DOI: 10.1016/j.cell.2017.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Aged Stem Cells Reprogram Their Daily Rhythmic Functions to Adapt to Stress

Abstract: Normal homeostatic functions of adult stem cells have rhythmic daily oscillations that are believed to become arrhythmic during aging. Unexpectedly, we find that aged mice remain behaviorally circadian and that their epidermal and muscle stem cells retain a robustly rhythmic core circadian machinery. However, the oscillating transcriptome is extensively reprogrammed in aged stem cells, switching from genes involved in homeostasis to those involved in tissue-specific stresses, such as DNA damage or inefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
200
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(218 citation statements)
references
References 57 publications
15
200
0
Order By: Relevance
“…Another two recent studies show that epidermal as well as skeletal muscle stem cells retain robust circadian rhythms upon aging, but that the set of oscillatory output gene changes from genes involved in homeostasis to tissuespecific stress-associated genes involved in DNA damage and inefficient autophagy [73,74]. The authors could prevent age-associated rewiring of the circadian transcriptome by long-term caloric restriction in aged mice, which is line with an earlier found correlation between low-fat diet and reduced aging [73,75]. This means that stem cells can adapt their circadian transcriptome to different conditions of metabolic states and organ-specific stresses.…”
Section: Es Cells Differentiated Cellsmentioning
confidence: 99%
“…Another two recent studies show that epidermal as well as skeletal muscle stem cells retain robust circadian rhythms upon aging, but that the set of oscillatory output gene changes from genes involved in homeostasis to tissuespecific stress-associated genes involved in DNA damage and inefficient autophagy [73,74]. The authors could prevent age-associated rewiring of the circadian transcriptome by long-term caloric restriction in aged mice, which is line with an earlier found correlation between low-fat diet and reduced aging [73,75]. This means that stem cells can adapt their circadian transcriptome to different conditions of metabolic states and organ-specific stresses.…”
Section: Es Cells Differentiated Cellsmentioning
confidence: 99%
“…Circadian clocks are master regulators of metabolism (18), and it was speculated that at least some of the beneficial outcomes of CR are due to the effect on the clock (2,3). Recent analysis of circadian rhythms of mRNA abundance in the liver and skeletal muscles of young and old mice fed ad libitum (AL) or CR diets identifies a significant reprogramming of the circadian transcriptome by aging and CR (16,19), supporting the importance of the interaction between biologic clocks, diet, and aging.…”
mentioning
confidence: 99%
“…Our study has identified that hippocampal NSCs exhibit early cellular aging ( Figure 3). To extend this phenotype, we compared NSC transcriptomes from the mature hippocampus (merged quiescent and active states) with published advanced age hematopoietic -hSC (Sun et al, 2014), muscle -mSC (Liu et al, 2013) and epidermal -eSC (Solanas et al, 2017) stem cell transcriptome datasets ( Figure 4A, Table S9). Fisher's exact tests were run on respective DEs to determine the degree of age-associated gene expression convergence between NSCs and other stem cell compartments.…”
Section: Consensus Signatures Of Stem Cell Agingmentioning
confidence: 99%